Psychometric Properties of the Internet Gaming Disorder Scale-Short-Form (IGDS9-SF): Systematic Review - Lok Y J Poon; Hector W H Tsang; Tsan Y J Chan; Sze W T Man; Lok Y Ng; Yi L E Wong; Chung-Ying Lin; Chi-Wen Chien; Mark D Griffiths; Halley M Pontes; Amir H Pakpour (JMIR Publications, 2021)
BackgroundThe Internet Gaming Disorder Scale-Short-Form (IGDS9-SF) is among the best with regard to its psychometric properties. Therefore, clinical psychologists are likely guided to use the IGDS9-SF if they want to assess or screen the disordered gaming in their practice. However, the information, especially psychometric evidence, concerning the IGDS9-SF has not been fully examined and summarized. ObjectiveThis systematic review evaluated the psychometric properties of different language versions of the IGDS9-SF and assessed its methodological quality in order to improve the clinicians' understanding of the IGDS9-SF and facilitate its use. MethodsSystematic literature searches were carried out using Embase, MEDLINE, PsycINFO, PubMed, ScienceDirect, Scopus, and Web of Science. The review included English-language studies of any research design that have reported at least one psychometric property of the IGDS9-SF, as defined by the COnsensus-based Standards for the selection of health status Measurement INstrument (COSMIN), and have aimed at testing the psychometric properties of the IGDS9-SF. ResultsIn total, 21 studies comprising 15 language versions of the IGDS9-SF were included. Overall, the IGDS9-SF showed adequate internal consistency (although some items did not have satisfactory item-total correlation [IT]), excellent criterion validity, and the ability to distinguish different subgroups with measurement invariance being supported across gender and age. In terms of factor structure, the IGDS9-SF was shown to have a unidimensional factor structure across all 21 studies. ConclusionsAlthough there is insufficient evidence regarding the responsiveness and properties of the IGDS9-SF using item response theory, the existing evidence supports its use in assessing disordered gaming among individuals.